Gold-Nanoparticle Decorated Graphene-Nanostructured Polyaniline Nanocomposite-Based Bienzymatic Platform for Cholesterol Sensing. (11th November 2012) - Saini, Deepshikha; Chauhan, Ruchika; Solanki, Pratima R.; Basu, T.
Abstract : A novel nanobiocomposite bienzymatic amperometric cholesterol biosensor, coupled with cholesterol oxidase (ChOx) and horseradish peroxidase (HRP), was developed based on the gold-nanoparticle decorated graphene-nanostructured polyaniline nanocomposite (NSPANI-AuNP-GR) film which was electrochemically deposited onto indium-tin-oxide (ITO) electrode from the nanocomposite (NSPANI-AuNP-GR) dispersion, as synthesized by in situ polymerization technique. The gold nanoparticle-decorated graphene-nanostructured polyaniline nanocomposite (NSPANI-AuNP-GR) offers an efficient electron transfer between underlining electrode and enzyme active center. The bienzymatic nanocomposite bioelectrodes ChOx-HRP/NSPANI-AuNP-GR/ITO have exhibited higher sensitivity, linearity, and lowerK m value than monoenzymatic bioelectrode (ChOx/NSPANI-AuNP-GR/ITO). It is inferred that bienzyme-based nanobioelectrodes offer wider linearity (35 to 500 mg/dL), higher sensitivity (0.42 μ AmM −1 ), low km value of 0.01 mM and higher accuracy for testing of blood serum samples than monoenzyme system. Mechanism of the overall biochemical reaction has been proposed to illustrate the enhanced biosensing performance of the bienzyme system. The novelty of the electrode lies on reusability, extended shelf life, and accuracy of testing blood serum samples.